An ex vivo functional biomarker of treatment response in pediatric low-grade glioma - Nichole M. Artz; Breanna Mann; Aaron Ebbs; Rami Darawsheh; Rajaneekar Dasari; Adebimpe Adefolaju; Noah Bell; Dimitri Trembath; Dominique Higgins; Scott Elton; Albert Baldwin; Shawn Hingtgen; et al. (PLoS ONE, 2026)
Children with subtotally resected pediatric low-grade glioma (pLGG) often face multiple lines of treatment, which are seldom capable of eliminating the entire tumor. Genomics-based biomarkers are often used to select targeted therapies, but this paradigm only yields overall response rates of ~50%. Functional precision medicine (FPM), where patient-specific therapeutic efficacy is evaluated by directly treating individuals’ tumor outside their body, can predict individualized drug responses for some cancers, but pLGG is notoriously difficult to maintain outside the body, limiting development of FPM for pLGG. We describe the first platform that can maintain, treat, and analyze zero-passage pLGG tumor tissue ex vivo , facilitating FPM testing. Here, we tested pLGG tumors on our previously validated Screening Live Cancer Explants (SLiCE) platform, which allows engraftment and testing of diverse CNS tumor types atop organotypic brain slice cultures (OBSCs). After ensuring reproducible engraftment and maintenance of all three living pLGG tumor tissues on SLiCE, we measured MAPK pathway response to targeted therapies via immunoblotting. In the tested BRAF KIAA1549 fusion+ tumor, Western blot demonstrated maintenance of expected paradoxical MAPK upregulation in response to dabrafenib treatment. We then measured tumor response to targeted therapies on SLiCE. As expected, none of the BRAF KIAA1549 fusion+ pLGG tumors were sensitive to dabrafenib treatment. Two out of the three tumors demonstrated predicted sensitivity to trametinib, whereas one tumor did not. While no clinical correlates were measured in this proof-of-concept study, this mixed response to MEK inhibition on SLiCE is representative of heterogeneous real-world clinical responses. Together, these data demonstrate the feasibility of SLiCE to become a new functional biomarker of response in a tumor type where functional models are exceptionally rare, establishing a foundation for future individualized treatment strategies.